Gathering momentum for the way ahead: fifth report of the Lancet Standing Commission on Liver Disease in the UK. Issue 10162 (1st December 2018) - Williams, Roger; Alexander, Graeme; Aspinall, Richard; Batterham, Rachel; Bhala, Neeraj; Bosanquet, Nick; Severi, Katherine; Burton, Anya; Burton, Robyn; Cramp, Matthew E; Day, Natalie; Dhawan, Anil; et al.
Summary: This report presents further evidence on the escalating alcohol consumption in the UK and the burden of liver disease associated with this major risk factor, as well as the effects on hospital and primary care. We reiterate the need for fiscal regulation by the UK Government if overall alcohol consumption is to be reduced sufficiently to improve health outcomes. We also draw attention to the effects of drastic cuts in public services for alcohol treatment, the repeated failures of voluntary agreements with the drinks industry, and the influence of the industry through its lobbying activities. We continue to press for reintroduction of the alcohol duty escalator, which was highly effective during the 5 years it was in place, and the introduction of minimum unit pricing in England, targeted at the heaviest drinkers. Results from the introduction of minimum unit pricing in Scotland, with results from Wales to follow, are likely to seriously expose the weakness of England's position. The increasing prevalence of obesity-related liver disease, the rising number of people diagnosed with type 2 diabetes and its complications, and increasing number of cases of end-stage liver disease and primary liver cancers from non-alcoholic fatty liver disease make apparent the need for an obesity strategy for adults. We also discuss the important effects of obesity and alcohol on disease progression, and the increased risk of the ten most common cancers (including breast and colon cancers). A new in-depth analysis of the UK National Health Service (NHS) and total societal costs shows the extraordinarily large expenditures that could be saved or redeployed elsewhere in the NHS. Excellent results have been reported for new antiviral drugs for hepatitis C virus infection, making elimination of chronic infection a real possibility ahead of the WHO 2030 target. However, the extent of unidentified cases remains a problem, and will also apply when new curative drugs for hepatitis B virus become available. We also describe efforts to improve standards of hospital care for liver disease with better understanding of current service deficiencies and a new accreditation process for hospitals providing liver services. New commissioning arrangements for primary and community care represent progress, in terms of effective screening of high-risk subjects and the early detection of liver disease.